Comparison of salinity and drought stress effects on abscisic acid metabolites activity of cytokinin oxidase/dehydrogenase and chlorophyll levels in radish audtabacco - Vankova, Radomira; Gaudinova, Alena; Dobrev, Petre; Malbeck, Jiri; Haisel, Daniel; Motyka, Vaclav (Ecological Questions, 2011)
Stronger negative impact of salinity (100 mM NaCl for 4 days) on radish plants in comparison with tobacco ones, correlated with more profound decrease of bioactive cytokinins and higher elevation of activity of the main cytokinin degrading enzyme cytokinin oxidase/dehydrogenase and abscisic acid in the former species.